Analisa Kebijakan Luar Negeri Amerika Serikat Dalam Memberantas Terorisme pada Masa Pemerintahan Presiden George W. Bush - Mumtazinur, Mumtazinur (Al-Ijtima`i: International Journal of Government and Social Science, 2016)
This article revisits the foreign policy of the United States of America since 9/11 under the governance of George W.Bush. It begins first by describing the linkage between international security and international terrorism, and then the influence of hawkish politics to terrorism foreign policy of the United States of America. This article stresses the stance of America in the war of terrorism with the military forces and how it affect to create security for all creatures in the world.